2003
DOI: 10.3354/ame031033
|View full text |Cite
|
Sign up to set email alerts
|

What limits bacterial production in the suboxic region of permanently ice-covered Lake Bonney, Antarctica?

Abstract: Bacterial production assays (thymidine incorporation rates) were used to evaluate the activity of heterotrophic bacteria at the chemocline region in both the East (ELB) and West (WLB) Lobes of permanently ice-covered Lake Bonney, in the Taylor Valley of Antarctica. The magnitude of activity varied dramatically within the depth interval of 1 to 2 m from moderate to very low levels below the chemocline, especially in the East Lobe, where chemical distributions indicate the absence of a normally functioning nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 32 publications
(35 reference statements)
1
25
0
Order By: Relevance
“…Samples were collected in November and December of 1999 and 2000. Water was collected from a central station in each lobe of Lake Bonney using trace metal clean sampling techniques (Bruland et al 1979) as described previously (Ward et al 2003). Briefly, a peristaltic pump equipped with acid-leached C-Flex tubing (Cole Parmer) was used to pump water from depth through an acid-cleaned teflon tube which was lowered through a hole drilled through the 4 m thick permanent ice cover.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Samples were collected in November and December of 1999 and 2000. Water was collected from a central station in each lobe of Lake Bonney using trace metal clean sampling techniques (Bruland et al 1979) as described previously (Ward et al 2003). Briefly, a peristaltic pump equipped with acid-leached C-Flex tubing (Cole Parmer) was used to pump water from depth through an acid-cleaned teflon tube which was lowered through a hole drilled through the 4 m thick permanent ice cover.…”
Section: Methodsmentioning
confidence: 99%
“…Polyethylene-lined trilaminate bags (Pollution Measurement Corporation) were used for sample collection and incubation (Ward et al 2003). Bags were acidwashed and flushed with N 2 gas prior to use.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have shown that little microbial activity of any kind occurs in the deep brine of ELB despite the presence of viable cells (Priscu 1997;Ward and Priscu 1997). This lack of microbial metabolism may be the result of metal toxicity associated with the deep brine (Ward et al , 2005 or thermodynamic constraints that have evolved over time (Lee et al 2004). In the absence of modern activity consistent with the observed N 2 O depth distribution, it has been suggested that the extreme N 2 O supersaturation in ELB may be a biogeochemical relict from past microbial activity that was present during the climate-driven evolution of the lake Priscu 1997).…”
mentioning
confidence: 99%